2013
DOI: 10.1002/jgrd.50860
|View full text |Cite
|
Sign up to set email alerts
|

Varying roles of ENSO and SAM on the Antarctic Peninsula climate in austral spring

Abstract: [1] Recent studies have identified a significant warming trend across West Antarctica and the Antarctic Peninsula, which is likely linked to tropical forcing. Here we investigate temporal variations in El Niño-Southern Oscillation (ENSO)-related tropical forcing and Southern Annular Mode (SAM)-related forcing on the Amundsen-Bellingshausen Seas Low and the regional climate during austral spring. We find a spatial dependency regarding the impacts each of these climate modes have on the Antarctic Peninsula: rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 44 publications
7
133
1
Order By: Relevance
“…ENSO also plays a role through the modulation of the South Pacific Convergence Zone (IPCZ); however, the relationship between snow accumulation and both SAM and ENSO is not temporally stable (Thomas et al, 2008Goodwin et al, 2016). It has been suggested that the coupling between these two modes of variability modulates snow accumulation in the AP (Clem and Fogt, 2013) and may explain the acceleration since the 1990s when both modes are inphase. The increased snowfall has also been linked to warming sea surface temperatures in the western Pacific , an area not associated with ENSO, and with the phase changes of the Pacific Decadal Oscillation (PDO), which exhibits major phase shifts in the late 1940s and mid1970s (Goodwin et al, 2016).…”
Section: Antarctic Peninsula (Ap)mentioning
confidence: 99%
“…ENSO also plays a role through the modulation of the South Pacific Convergence Zone (IPCZ); however, the relationship between snow accumulation and both SAM and ENSO is not temporally stable (Thomas et al, 2008Goodwin et al, 2016). It has been suggested that the coupling between these two modes of variability modulates snow accumulation in the AP (Clem and Fogt, 2013) and may explain the acceleration since the 1990s when both modes are inphase. The increased snowfall has also been linked to warming sea surface temperatures in the western Pacific , an area not associated with ENSO, and with the phase changes of the Pacific Decadal Oscillation (PDO), which exhibits major phase shifts in the late 1940s and mid1970s (Goodwin et al, 2016).…”
Section: Antarctic Peninsula (Ap)mentioning
confidence: 99%
“…In particular, Clem and Fogt (2013) demonstrated that the greater breadth of the ASL, stretching from the Ross through the Bellingshausen Seas, leads to uniform impacts on temperature, wind, and pressure across the Antarctic Peninsula in austral spring. In other cases, smaller spatial extents of the ASL tend to only influence the western Antarctic Peninsula, while the northeastern Antarctic Peninsula is more strongly modulated by variations in the SAM.…”
Section: Impacts Of the Amundsen Sea Low On Antarctic Climatementioning
confidence: 99%
“…However, this mode of climate variability has a marked impact on the southeast Pacific sector of the Southern Ocean via both atmospheric and oceanic teleconnections (Meredith et al, 2008b;Turner, 2004;Yuan, 2004 Niño and/or negative SAM conditions result in the greater local preponderance of colder, drier air masses. The coincident phasing of these two atmospheric modes can thus amplify or dampen the atmospheric circulation changes and climatic anomalies at the WAP (Clem and Fogt, 2013;Fogt and Bromwich, 2006;Stammerjohn et al, 2008b).…”
Section: Water Masses Circulation and Variability At The Wapmentioning
confidence: 99%